2022
DOI: 10.48550/arxiv.2207.08952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stellar Energetic Particle Transport in the Turbulent and CME-disrupted Stellar Wind of AU~Microscopii

Abstract: Energetic particles emitted by active stars are likely to propagate in astrospheric magnetized plasma turbulent and disrupted by the prior passage of energetic Coronal Mass Ejections (CMEs). We carried out test-particle simulations of ∼ GeV protons produced at a variety of distances from the M1Ve star AU Microscopii by coronal flares or travelling shocks. Particles are propagated within the largescale quiescent three-dimensional magnetic field and stellar wind reconstructed from measured magnetograms, and with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…On the other hand, previous stellar wind simulations including CMEs (Alvarado-Gómez et al 2018) have suggested that strong solar-like CMEs may be suppressed by a largescale dipole stellar magnetic field of 75 G which would affect the corresponding stellar energetic particle fluxes. Fraschetti et al (2022) showed for the AU Mic system how the stellar energetic particle flux distribution reaching the planetary orbits is strongly altered by the passage of a CME. To complicate matters further, solar CME-CME interactions account for more than 25% of the major geomagnetic storms observed (Zhang et al 2007).…”
Section: Maximum Stellar Energetic Particle Momentummentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, previous stellar wind simulations including CMEs (Alvarado-Gómez et al 2018) have suggested that strong solar-like CMEs may be suppressed by a largescale dipole stellar magnetic field of 75 G which would affect the corresponding stellar energetic particle fluxes. Fraschetti et al (2022) showed for the AU Mic system how the stellar energetic particle flux distribution reaching the planetary orbits is strongly altered by the passage of a CME. To complicate matters further, solar CME-CME interactions account for more than 25% of the major geomagnetic storms observed (Zhang et al 2007).…”
Section: Maximum Stellar Energetic Particle Momentummentioning
confidence: 99%
“…We relate the maximum energy of the stellar energetic particles accelerated by stellar flares to stellar magnetic field strength, following Rodgers-Lee et al (2021a), and show how this can be related to stellar X-ray luminosity. Previous studies have investigated the distribution of stellar energetic particles in the Trappist-1 and AU Mic systems (Fraschetti et al 2019(Fraschetti et al , 2022. In the latter case, following a perturbation of the interplanetary medium by a coronal mass ejection (CME).…”
mentioning
confidence: 99%